Study on farmers post-adoption behaviour for soil and water conservation practices in South-eastern Rajasthan - Kumar, ASHOK; ALI, SHAKIR; KUMAR, KULDEEP; SINGH, R. K. (Journal of Soil and Water Conservation, 2020)
The post adoption behavior of watershed beneficiaries’ farmers towards soil and water conservation practices (technologies) in South-eastern Rajasthan was measured in terms of continue-adoption, disadoption, diffusion and technological gap as perceived by the farmers apart from identifying factors influencing the extent of adoption. The results revealed that 79% of the Soil and water conservation (SWC) technologies were adopted by the beneficiary farmers even after withdrawal of selected watershed projects in the region while, 21% of the SWC technologies discontinued by the farmers due to various reasons. It was also found that 9% of SWC technologies were adopted with technological gap. The diffusion of adopted SWC technologies indicates that 42% farmers diffused the technology in nearby areas for the conservation of natural resources. The pooled analysis of all the watersheds data show that farm size, education and scientific orientation of farmers positively affect extent of adoption whereas material possession was having negative relation with the adoption extent in the region. Variation in factors affecting extent of adoption in the watersheds located in the same region suggested that any technological intervention for soil and water conservation in an area ought to begin with understanding of local factors which may influence technology adoption.